On minimal non- MSP -groups - Guo, P.; Zhang, Xirong (Ukrains’kyi Matematychnyi Zhurnal, 2011)
A finite group G is called an MSP-group if all maximal subgroups of the Sylow subgroups of G are Squasinormal in G. In this paper, wc give a complete classification of those groups which are not MSP-groups but whose proper subgroups are all MSP-groups.